3+1/3x-2/3-2x-x/2+x/3=1/6x

Simple and best practice solution for 3+1/3x-2/3-2x-x/2+x/3=1/6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+1/3x-2/3-2x-x/2+x/3=1/6x equation:



3+1/3x-2/3-2x-x/2+x/3=1/6x
We move all terms to the left:
3+1/3x-2/3-2x-x/2+x/3-(1/6x)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 6x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
1/3x-2x-x/2+x/3-(+1/6x)+3-2/3=0
We add all the numbers together, and all the variables
-2x+1/3x-x/2+x/3-(+1/6x)+3-2/3=0
We get rid of parentheses
-2x+1/3x-x/2+x/3-1/6x+3-2/3=0
We calculate fractions
We do not support expression: x^3

See similar equations:

| 2w-6=6(w+3) | | 2(y+4)-4y=16 | | 8x2-4×=-2 | | 3x^2+x-270=0 | | (3m-5)=0 | | 2(x-3)-3(1-2x)=3(2-x)-2(5-3x) | | 1.8=2.1h+5.7+4.6h | | 0.2x+0.6/0.4x+01=0.8 | | 1.8=2.1h+5.7+4.6 | | -6.1p=-24.4 | | 12x+3=4x+37 | | 12x+3=4x37 | | 12n^2+13n+3=0 | | n+34=212 | | +3x-4=2x+1 | | 6•+3y=12 | | 3x=221x3 | | 6v^2-12+18=0 | | 2=3h-5.8-3.5h | | r2−8r=−8 | | 9p-4=-189p−4=−18 | | 3x-3x=7-7 | | 8q-6=10 | | 2a^2-7=43 | | 5(a+3)=24 | | 2d^=162 | | 9.1=0.3(h−–3)−–6.1 | | x*1.09=170 | | (x*1.09)=170 | | -4=2m/5 | | 0.3/2=15/x | | (3/10)=(x/9) |

Equations solver categories